HUBUNGAN ANTARA KOMPETENSI KEWIRAUSAHAAN KEPALA MADRASAH DENGAN TINGKAT KESEJAHTERAAN GURU MADRASAH TSANAWIYAH SE-KECAMATAN DUA BOCCOE KABUPATEN BONE - Ikhsana, A. Nurul; Syamsudduha, Siti; Tahir, M. Yusuf (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: The Relationship Between The Entrepreneurial Competence of Madrasah Principals and The Welfare Level of Madrasah Teachers This article aims to test: 1) The level of correlation between the innovation ability of madrasah principals with the walfare of Madrasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency; 2) The level of correlation between the ability to work hard at madrasah principals with the walfare of Madrasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency; 3) The level of correlation between the ability of madrasah principals to provide motivation with the welfare of Madarasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency. The type of research used is correlational research with a positivistic-quantitative methodological approach with sociological and psychological studies. The population in this study were 77 teachers. Data collection was done by distributing questionnaires to respondents and analyzed using product moment correlation analysis. The results sho wed that: (1) There is a positive correlation between the innovation ability of madrasah principals with the welfare of Madrasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency; (2) There is a positive correlation between the ability to work hard at Madrasah principals with the welfare of Madrasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency; (3) There is a positive correlation between the ability of madrasah principals to provide motivation with the welfare of Madrasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency. Abstrak: Hubungan antara Kompetensi Kewirausahaan Kepala Madrasah dengan Tingkat Kesejahteraan Guru Madrasah Artikel ini bertujuan untuk menguji: (1) Tingkat hubungan antara kemampuan inovasi kepala madrasah dengan kesejahteraan guru Madrasah Tsanawiyah se-Kecamtan Dua Boccoe Kabupaten Bone; (2) Tingkat hubungan antara kemampuan bekerja keras kepala madrasah dengan kesejahteraan guru Madrasah Tsanawiyah se-Kecamatan Dua Boccoe Kabupaten Bone; (3) Tingkat hubungan antara kemampuan kepala madrasah dalam memberikan motivasi dengan kesejahteraan guru Madrasah Tsanawiyah se-Kecamatan Dua Boccoe Kabupaten Bone. Jenis penelitian yang digunakan adalah penelitian korelasional dengan pendekatan metodologi postivistik-kuantitatif dengan kajian sosiologis dan psikologis. Populasi dalam penelitian ini adalah 77 guru. Pengumpulan data dilakukan dengan menyebarkan angket kepada responden dan dianalisis menggunakan analisis korelasi product moment. Hasilnya menunjukkan bahwa: (1) Terdapat hubungan positif antara kemampuan berinovasi kepala madrasah dengan kesejahteraan guru Madrasah Tsanawiyah se-Kecamatan Dua Boccoe Kabupaten Bone; (2) Terdapat hubungan positif antara kemampuan bekerja keras kepala madrasah dengan kesejahteraan guru Madrasah Tsanawiyah se-Kecamatan Dua Boccoe Kabupaten Bone; 3) Terdapat hubungan positif antara kemampuan kepala madrasah memberikan motivasi dengan kesejahteraan guru Madrasah Tsanawiyah se-Kecamatan Dua Boccoe Kabupaten Bone.